Eksplorasi Pemikiran M. Nasroen, Soenoto, dan R. Parmono dalam Perkembangan Filsafat Nusantara - Fitri Alfariz; Rr Yudiswara Ayu Permatasari (Jurnal Filsafat Indonesia, 2022)
Nusantara philosophy is still looking for the most ideal form. M. Nasroen, R. Parmono, and Soenoto as ‘pioneers’ of Indonesian philosophy have provided good thought for the developmentof nusantara philosophy in Indonesia. Although in the development of Indonesian philosophy and nusantara philosophy is considered the same, but the two discourses still cannot be agreed upon. The development of nusantara philosophy involves various thoughts. Therefore, this study attempts to provide a description of the thoughts of the ‘pioneers’ of Indonesian philosophy inhopes of seeing how far the development of nusantara philosophy. The method used is qualitative research with comparative methods. Comparisons from the three figures found that M. Nasroen, R. Parono, and Soenoto have their own thoughts on Indonesian philosophy that have not answered the boundaries and embrace of thinking that develops beyond the geographical linesof Indonesia. It is also found that their thoughts are related to philosophy as a process or product of a culture. Through the research it was found that the thought of the three figures had manyinfluences on the current concepts of nusantara philosophy that led closer to the ideal form of nusantara philosophy